2023
DOI: 10.3389/fpubh.2023.1123835
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of elder neglect in the community-dwelling Chinese population: New evidence from the CLHLS study

Abstract: BackgroundThis study aimed to explore the prevalence of elder neglect (EN) and its associated factors among community-based Chinese older adults.MethodsWe used data from the 2018 phase of a nationwide cross-sectional study, the Chinese Longitudinal Healthy Longevity Survey (CLHLS), which recruited 15,854 older adults to complete the study interviews that incorporated six dimensions of EN, namely, life neglect, social isolation, medical neglect, poor living situation, family neglect, and social neglect. Multiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Information gathered by the project included fundamental characteristics, socioeconomic features, behavioural habits, dietary status, and physical health status of the elderly. More detailed descriptions of the CLHLS project can be found elsewhere [28][29][30]. The CLHLS received ethical approval from the Biomedical Ethics Committee of Peking University, China (IRB00001052-13074).…”
Section: Study Populationmentioning
confidence: 99%
“…Information gathered by the project included fundamental characteristics, socioeconomic features, behavioural habits, dietary status, and physical health status of the elderly. More detailed descriptions of the CLHLS project can be found elsewhere [28][29][30]. The CLHLS received ethical approval from the Biomedical Ethics Committee of Peking University, China (IRB00001052-13074).…”
Section: Study Populationmentioning
confidence: 99%
“…A China-based study conducted in 2018 found that older individuals with chronic diseases were vulnerable to neglect in various aspects of their lives, including life neglect, medical neglect, and neglect in their residential environment. The study also revealed that older individuals with better cognitive abilities were less likely to experience neglect, while a decline in their daily activity capacity was associated with a higher risk of elder neglect [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) divided elder abuse into five categories, one of which is elder neglect (1). It is described as a caregiver's failure to provide basic or essential services to an older adult or protect them from injury (2). Elder neglect could be detrimental to physical and mental health.…”
Section: Introduction 1backgroundmentioning
confidence: 99%